2023
DOI: 10.1039/d3ra02873a
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of 2-nitrophenols in annulations with aryl isothiocyanates towards the synthesis of 2-aminobenzoxazoles

Abstract: A general method to afford 2-aminobenzoxazoles by the annulation of 2-nitrophenols with aryl isothiocyanates is firstly reported. The tolerance of an array of useful functionalities is observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…5 The use of such nitroarenes avoids the pre-functionalization of ortho C–H bonds to nitroarenes prior to cyclization. 6 It should also be noted that elemental sulfur is often essential to promoting the transformations of N , N -dialkyl-3-nitroanilines. 7 As previous reports suggested that the C–H bonds ortho to nitro groups and para to N , N -dialkylamino groups are nucleophilic enough to react with sulfur-containing electrophiles, herein we report our attempts to develop a method for the cyclization of N , N -dialkyl-3-nitroanilines with aryl isothiocyanates.…”
Section: Introductionmentioning
confidence: 99%
“…5 The use of such nitroarenes avoids the pre-functionalization of ortho C–H bonds to nitroarenes prior to cyclization. 6 It should also be noted that elemental sulfur is often essential to promoting the transformations of N , N -dialkyl-3-nitroanilines. 7 As previous reports suggested that the C–H bonds ortho to nitro groups and para to N , N -dialkylamino groups are nucleophilic enough to react with sulfur-containing electrophiles, herein we report our attempts to develop a method for the cyclization of N , N -dialkyl-3-nitroanilines with aryl isothiocyanates.…”
Section: Introductionmentioning
confidence: 99%